The quality of clinical maternal and neonatal healthcare – a strategy for identifying ‘routine care signal functions’ - Brenner, Stephan; Allegri, Manuela De; Gabrysch, Sabine; Chinkhumba, Jobiba; Sarker, Malabika; Muula, Adamson S. (Plos One, 2016)
Includes bibliographical references (page 16-19).